Designing a mobile application testing model - Tan, Ping Ping; Hamizan, Sharbini; Wee, Bui Lin; Mun, Vikki Tan Wyn; Azlina, Ahmadi Julaihi (Universiti Malaysia Sarawak, 2013)
In order to ensure that the software developed is at its highest quality, testing should be done all through the software life cycle and should start as early as possible. Therefore, for our previous mobile application development project, V-Model (a software testing model) was adopted as currently there is no specific testing model for mobile application. Unfortunately, we faced with a lot of challenges, similar to the challenges faced by other mobile application project, namely physical factors, network connections, testing equipment, system bug versus mobile device bug and multiple mobile platform and versioning. Even though the main objective is to test the mobile application, mobile application testing cannot be separated from testing on different mobile devices. Although solutions had been proposed to solve a few common mobile application testing challenges, there is still no clear testing model for mobile application. This paper presents the criteria to be considered when designing a testing model for mobile application.